Development of Google Sites-Based Learning Media for Islamic Education Learning in Elementary Schools - Aeni, Ani Nur; Abdullah, Mulyana; Fitriyatunnisa, Fifit; Wulan, Neng; Zahra, Santika Az (Al-Hayat: Journal of Islamic Education, 2024)
This study aims to develop a Google Sites-based learning media called ATM-KU (Praiseworthy Morals Building Noble Morals) for grade II elementary school students in Islamic religious education. Google sites-based learning media ATM-KU aims to improve moral understanding in a fun and interactive way, addressing the challenge of teaching morals to primary school students, which is often considered boring. By utilising Google Sites, it is hoped that students will be more interested and actively involved in the learning process. The primary goal is to create a compelling and exciting learning medium to increase students' interest and understanding of morals in Islamic Religious Education. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Literature studies and observations are conducted in the analysis stage to understand students' needs. An attractive and child-friendly user interface, features, and interactions are developed at the design stage. In the development stage, content and features are created according to the design, followed by initial testing. During implementation, Google Sites is used in the classroom learning process. At the evaluation stage, student responses are collected through questionnaires to assess the effectiveness of the media. The results show that ATM-KU effectively increases students' interest in Islamic Religious Education, especially in the material "Let's Have a Commendable Character!" Students responded positively to this media. However, the research is limited to one class, indicating the need for broader implementation. These findings demonstrate the originality of combining Google Sites technology with interactive methods for teaching morals.